Palmatine ameliorates nephrotoxicity and hepatotoxicity induced by gentamicin in rats. (4th May 2021) - Khaksari, Mehdi; Esmaili, Samira; Abedloo, Reyhane; Khastar, Hossein
Abstract: The aim of this study was to investigate the effects of palmatine on gentamicin toxicity. Rats arranged in four groups: 1- Sham, 2- GM, 3- & 4- GM + palmatine (50 & 100 mg/kg). Gentamicin led to increase in plasma AST, ALT, BUN and creatinine. In addition, fractional excretion of Na and K were increased and urine flow rate and creatinine clearance were decreased in gentamicin group. Liver and renal tissues malondialdehyde were increased, and glutathione was decreased in GM group. TUNEL assay showed induction of apoptosis in liver and kidney in GM group. Palmatine treatment caused reduction in plasma AST, ALT, urine flow rate, creatinine clearance, renal and hapatic malondialdehyde, apoptosis and increase in renal and hapatic glutathione, fractional excretion of Na and K, plasma BUN and creatinine in contrast to GM group. Our data showed palmatine reduced hepatotoxicity and nephrotoxicity by inhibition of oxidative stress and apoptosis.